Neurochemical features of boar lumbosacral dorsal root ganglion neurons and characterization of sensory neurons innervating the urinary bladder trigone. Issue 2 (6th December 2012) - Russo, D.; Clavenzani, P.; Sorteni, C.; Bo Minelli, L.; Botti, M.; Gazza, F.; Panu, R.; Ragionieri, L.; Chiocchetti, R.
Abstract Porcine lumbosacral dorsal root ganglion (DRG) neurons were neurochemically characterized by using six neuronal markers: calcitonin gene‐related peptide (CGRP), substance P (SP), neuronal nitric oxide synthase (nNOS), neurofilament 200kDa (NF200), transient receptor potential vanilloid 1 (TRPV1), and isolectin B4 (IB4) from Griffonia simplicifolia. In addition, the phenotype and cross‐sectional area of DRG neurons innervating the urinary bladder trigone (UBT) were evaluated by coupling retrograde tracer technique and immunohistochemistry. Lumbar and sacral DRG neuronal subpopulations were immunoreactive (IR) for CGRP (30 ± 3% and 29 ± 3%, respectively), SP (26 ± 8% and 27 ± 12%, respectively), nNOS (21 ± 4% and 26 ± 7%, respectively), NF200 (75 ± 14% and 81 ± 7%, respectively), and TRPV1 (48 ± 13% and 43 ± 6%, respectively), and labeled for IB4 (56 ± 6% and 43 ± 10%, respectively). UBT sensory neurons, which were distributed from L2 to Ca1 DRG, had a segmental localization, showing their highest density in L4–L5 and S2–S4 DRG. Lumbar and sacral UBT sensory neurons expressed similar percentages of NF200 immunoreactivity (64 ± 33% and 58 ± 12%, respectively) but showed a significantly different immunoreactivity for CGRP, SP, nNOS, and TRPV1 (56 ± 9%, 39 ± 15%, 17 ± 13%, 62 ± 10% vs. 16 ± 6%, 16 ± 11%, 6 ± 1%, 45 ± 24%, respectively). Lumbar and sacral UBT sensory neurons also showed different IB4 labeling (67 ± 19% and 48 ± 16, respectively). Taken together, these data indicate that the lumbar and sacral pathways probably play different roles in sensory transmission from the UBT. The findings related to cell size also reinforced this hypothesis, because lumbar UBT sensory neurons were significantly larger than sacral ones (1, 112 ± 624 μm2 vs. 716 ± 421 μm2). J. Comp. Neurol. 521:342–366, 2013. © 2012 Wiley Periodicals, Inc.